Guilty Plea Decisions: Moving Beyond the Autonomy Myth. Issue 1 (25th August 2021) - Helm, Rebecca K.; Dehaghani, Roxanna; Newman, Daniel
Abstract: When a defendant pleads guilty to a criminal charge against them their conviction may be justified on the basis of autonomy rather than accuracy. In this context, autonomy can make the difference between a legitimate conviction and the breach of fundamental rights. However, autonomy in this context is not clearly defined. This article argues, based on philosophical conceptions of autonomy and empirical realities, that true autonomy is an ideal rather than a practical reality. It considers the level of autonomy necessary to legitimise a criminal conviction via plea, and suggests that current conceptions of autonomy are inadequate since they rely on a formalistic autonomy 'myth', presuming autonomy in the absence of threats. An analysis drawing on original empirical data from two studies demonstrates how autonomy may be being depleted to unacceptable levels in the current system. The article concludes by presenting reform proposals.